Assessing the Sustainable Development Goals and Its Application in Nigeria - Marcus Garvey ORJI (Britain International for Academic Research (BIAR) Publisher, 2024)
Sustainable development is maintaining a delicate balance between the human need to improve the way of life, maintain and guarantee the continuity of a business and feeling of well-being on one hand, and preserving natural resources and ecosystems, on which we and future generations depend. The United Nations Agenda 2030 is a plan of action for people, the planet, and prosperity. It also seeks to strengthen universal peace in greater freedom. The United Nations recognizes that eradicating poverty in all its forms and dimensions, including extreme poverty, is the greatest global challenge and an indispensable requirement for sustainable development. All countries and all stakeholders, acting in collaborative partnership, will implement this plan. UN is resolved to free the human race from the tyranny of poverty and want and to heal and secure our planet. UN is determined to take the bold and transformative steps that are urgently needed to shift the world onto a sustainable and resilient path. The 17 Sustainable Development Goals and 169 targets demonstrate the scale and ambition of this new universal Agenda. They seek to build on the Millennium Development Goals and complete what they did not achieve. They seek to realize the human rights of all and to achieve gender equality and the empowerment of all women and girls. They are integrated and indivisible and balance the three dimensions of sustainable development: the economic, social, and environmental. The objective of this study is to make a literature review of the 17 United Nations sustainable development goals in terms of concepts, institutional perceptions, and global challenges if any.